2020
DOI: 10.3390/nano10020341
|View full text |Cite
|
Sign up to set email alerts
|

Invasome: A Novel Nanocarrier for Transdermal Drug Delivery

Abstract: Invasomes are novel vesicular systems that exhibit improved transdermal penetration compared to conventional liposomes. These vesicles contain phospholipids, ethanol, and terpene in their structures; these components confer suitable transdermal penetration properties to the soft vesicles. The main advantages of these nanovesicles lie in their ability to increase the permeability of the drug into the skin and decrease absorption into the systemic circulation, thus, limiting the activity of various drugs within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 69 publications
(78 reference statements)
0
61
0
Order By: Relevance
“…In vitro tests showed a sustained release of methotrexate from the nanocarriers, whereas permeation studies demonstrated enhanced skin penetration of methotrexate after incorporation into SLNs. Photosensitive nanoformulations are also applied in acne treatment, a common inflammatory skin condition that can cause discomfort and visible, long-lasting scarring [127]. Examples of treatment agents for acne lesions are retinoids, such as tretinoin, efficiently encapsulated in liposomes [102] and nanoemulsions [110].…”
Section: Advances In Skin Formulationsmentioning
confidence: 99%
“…In vitro tests showed a sustained release of methotrexate from the nanocarriers, whereas permeation studies demonstrated enhanced skin penetration of methotrexate after incorporation into SLNs. Photosensitive nanoformulations are also applied in acne treatment, a common inflammatory skin condition that can cause discomfort and visible, long-lasting scarring [127]. Examples of treatment agents for acne lesions are retinoids, such as tretinoin, efficiently encapsulated in liposomes [102] and nanoemulsions [110].…”
Section: Advances In Skin Formulationsmentioning
confidence: 99%
“…In addition to providing an increased bioavailability and a more controlled drug release, our approach may also facilitate topical administration of thymol-invasomes due to the high permeability rate of invasomes through the skin [2,21,24].…”
Section: Succsessfull Preparation Of Invasomes Encapsulating the Terpmentioning
confidence: 99%
“…The application of soy lecithin liposomes comprising cinnamon oil was further shown to improve stability of the essential oil and extend the bactericidal action time [20]. In addition, the application of invasomes was particularly found to elevate the stability of the encapsulated compounds (reviewed in [24]).…”
Section: Growth-inhibition Zone Assay Shows Strong Bactericidal Activmentioning
confidence: 99%
See 1 more Smart Citation
“…A new phospholipid vesicle, invasome, has been presented as a system able to improve the permeation through the skin, thus decreasing absorption into the systemic circulation. 73 This innovative carrier is composed of phosphatidylcholine and terpenes that synergistically act with ethanol in disrupting the ordered structure of the stratum corneum to enhance the percutaneous permeation of the drug and to make phospholipid structures flexible. El-Nabarawi et al prepared dapsone-loaded invasomes for acne treatment, using different concentrations of various terpenes (limonene, cineole, fenchone and citral).…”
mentioning
confidence: 99%